Enriching entity grids and graphs with discourse relations: the impact in local coherence evaluation - Dias, Márcio de S.; Pardo, Thiago A. S. (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2015: Anais do X Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana, 2015)
This paper describes how discursive knowledge, given by the discursive theories RST (Rhetorical Structure Theory) and CST (Cross-document Structure Theory), may improve the automatic evaluation of local coherence in multi-document summaries. Two of the main coherence models from literature were incremented with discursive information and obtained 91.3% of accuracy, with a gain of 53% in relation to the original results.